Analysis of Gender Equality and Feminism of Main Character in Colette Movie - Lintang Ursita (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
The aim of the analysis is to analyse the gender equality and feminism that happened to the main character in Colette movie directed by Wash Westmoreland. The researcher focuses on every scenes and dialogues to make an easy way to analyse. The method of this analysis is descriptive qualitative method. The researcher also uses library research to support the data analysis. The theory that the researcher used to analysis gender equality is from McClain & Grossman (2009) and theory of Paludi (2017) for analysing feminism. The results of the study are: (1) Action of gender equality, the struggles, rebellion and speak up. (2) There are feminism movement that comes from the main character and also people around her, who is given her supports to get the gender equality. (3) The movie itself gives a lot of moral values in each part about gender equality and feminism that could be implemented in real life